Teacher’s Problems in Teaching English with a Level of Common European Framework of Reference for Students with Special Need (A Case Study in Inclusive School at SMP Al Irsyad Al Islamiyyah Purwokerto) - Rahayu Adinda Sahra; Khairunnisa Dwinalida (Ahmad Dahlan Journal of English Studies, 2024)
The purpose of this study was to find out the teacher’s problems in teaching English to students with special needs in the inclusive school of SMP Al Irsyad Al Islamiyyah Purwokerto. This research used qualitative methods with descriptive analysis techniques. The subject of the research was an English teacher who teaches students with special needs in ninth grades of SMP Al Irsyad Al Islamiyyah Purwokerto. This research was carried out using interviews, observation, and documentation as methodological triangulation to prove the reliability of the data. The data were analyzed by data reduction, data display, drawing conclusions, and data verification. The results indicated that teacher’s problems were caused by internal and external factors, including : 1) internal factors coming from the teacher herself consisting of time constraints and lack of teacher competence; 2) external factors come from several causes, including : a) problems from students consist of difficulties in the learning process, students' characteristics, students' academic performance, and difficulties interaction between students on a social level; b) problems from school management consist of a limited number of aide teachers and curriculum; c) problems from family environment consist of lack of parents’ attention.